2009
DOI: 10.1111/j.1651-2227.2008.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based consultations for parents of children with atopic dermatitis: results of a randomized controlled trial

Abstract: We found no effect of supplementing traditional treatment for childhood dermatitis with web-based consultations. This study showed that web consultations is feasible, but more research is needed to determine its effect on self-management skills, health outcome and resource use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(109 citation statements)
references
References 18 publications
1
106
0
2
Order By: Relevance
“…In a secondarycare setting, email consultation has been shown to facilitate access to a clinician, providing a communication channel. 29 In Norway, patients felt email consultation was positive in allowing them easier access to their general practice. 30 Impact of use has also been recognised in the US where physicians who were using email consultation with their patients expressed worries about email becoming a burden.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In a secondarycare setting, email consultation has been shown to facilitate access to a clinician, providing a communication channel. 29 In Norway, patients felt email consultation was positive in allowing them easier access to their general practice. 30 Impact of use has also been recognised in the US where physicians who were using email consultation with their patients expressed worries about email becoming a burden.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…10 Our study further applied the widely used and accessible smartphone for caregivers to email postoperative photos to the healthcare team. The feasibility of this mode of communication has been previously studied; [5][6][7][8] however, there has been no evidence to show that this communication is effective in educating caregivers regarding wound-healing or providing insight on when to return to the clinic or ER for evaluation. To our knowledge, this study is the first to demonstrate the effect of email communication and smartphone photography on aftercare, specifically unnecessary ER return rates among patients having undergone hypospadias repair.…”
Section: Discussionmentioning
confidence: 99%
“…4 Smartphones and the internet have become widely accessible commodities worldwide, making email a feasible method of communication between a patient's family and healthcare provider. 5,6 A recent study by Turk et al showed that photos from caregivers' video cameras for the followup assessment of children post-hypospadias repair decrease hospital anxiety for children and reduce clinic time at followup visits. 7 However, to date, there is no clear evidence that this mode of communication will have any effect on unnecessary postoperative ER visits.…”
Section: Introductionmentioning
confidence: 99%
“…14 Eleven studies were randomized controlled trials [11][12][13][14][15][16]18,[20][21][22][23][24][25] (Table S3). One study used the intervention for both screening and follow-up.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] All studies were from high income countries. Six studies (seven articles) were from the United States, 11,15,18,21,[23][24][25] two from the Netherlands, 17,22 and one from each of the following countries: Austria, 16 Canada, 20 Denmark, 26 Italy, 12 Norway, 13 Singapore, 19 and United Kingdom.…”
Section: Clinical Outcomesmentioning
confidence: 99%